The Necessity of Structural Changes in The Development of the National Economy - Norbekov Fazliddin (Universitas Muhammadiyah Sidoarjo, 2022)
This article analyzes the dynamics of economic growth in the economy of the Republic of Uzbekistan and identifies the sectors of the economy on the basis of which economic growth is provided in the country. In addition, the share of economic sectors in GDP and the dynamics of their growth rates were analyzed.